2009
DOI: 10.1016/j.chemosphere.2009.04.011
|View full text |Cite
|
Sign up to set email alerts
|

In vitro biotransformation of surfactants in fish. Part II – Alcohol ethoxylate (C16EO8) and alcohol ethoxylate sulfate (C14EO2S) to estimate bioconcentration potential

Abstract: Recent regulatory pressures (e.g., REACh, CEPA) requiring bioaccumulation assessments and the need for reduced animal use have increased the necessity for the development of in vitro-based methods to estimate bioaccumulation. Our study explored the potential use of subcellular and cellular hepatic systems to determine the biotransformation potential of two surfactants: octaethylene glycol monohexadecyl ether (C16EO8) and diethylene glycol monotetradecyl ether sulfate (C14EO2S). The subcellular systems tested w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 35 publications
1
25
0
3
Order By: Relevance
“…For fish it was demonstrated that in vitro tests can be used to determine the biotransformation potential of a species-compound combination (Fitzsimmons et al 2007;Dyer et al 2009). Nevertheless, confounding factors for the use biotransformation rate as traits are many, especially because biotransformation rates, just as sensitivity, strongly depend on the speciescompound combination and the physicochemical conditions (Fitzsimmons et al 2007).…”
Section: Toxicokineticsmentioning
confidence: 99%
“…For fish it was demonstrated that in vitro tests can be used to determine the biotransformation potential of a species-compound combination (Fitzsimmons et al 2007;Dyer et al 2009). Nevertheless, confounding factors for the use biotransformation rate as traits are many, especially because biotransformation rates, just as sensitivity, strongly depend on the speciescompound combination and the physicochemical conditions (Fitzsimmons et al 2007).…”
Section: Toxicokineticsmentioning
confidence: 99%
“…Standardized methods to measure in vivo biotransformation rates of high K OW chemicals in biota do not currently exist. Recently, in vitro biotransformation methods have been developed and tested to measure biotransformation rates (Han et al 2007; Dyer et al 2009). These methods are promising and have the potential to include biotransformation in bioaccumulation screening when methods for extrapolation of in vitro to in vivo biotransformation rates become available in the future.…”
Section: Tmf Alternativesmentioning
confidence: 99%
“…In vitro estimation of biotransformation potential —Biotransformation potential of fish has been investigated in liver slices (Schmieder et al 2000), whole liver homogenates (de Wolf et al 1993b), liver subfractions (Kolanczyk et al 1999; Dyer et al 2003; Perdu‐Durand et al 2004), isolated hepatocytes, and cell lines (Segner 1998; Cravedi et al 2001; Segner and Cravedi 2001; Dyer and Bernhard 2004). The xenobiotic metabolite pattern produced by fish hepatocytes in vitro is generally similar to that observed in vivo (Segner and Cravedi 2001).…”
Section: Review Of Alternative Approachesmentioning
confidence: 99%
“…Dyer et al (2003) applied an approach to derive a BCF cell for various surfactants using carp primary hepatocytes and cultured hepatocytes (PLHC‐1 cells). The rates of uptake and loss of the test chemical from the cellular systems were estimated assuming 1st‐order kinetics and the BCF in the cells determined by a ratio of uptake rate to the rate of loss.…”
Section: Review Of Alternative Approachesmentioning
confidence: 99%